2010
DOI: 10.1016/j.neuroimage.2009.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Modulating cortical connectivity in stroke patients by rTMS assessed with fMRI and dynamic causal modeling

Abstract: Data derived from transcranial magnetic stimulation (TMS) studies suggest that transcallosal inhibition mechanisms between the primary motor cortex of both hemispheres may contribute to the reduced motor performance of stroke patients. We here investigated the potential of modulating pathological interactions between cortical motor areas by means of repetitive TMS using functional magnetic resonance imaging (fMRI) and dynamic causal modeling (DCM). Eleven subacute stroke patients were scanned 1-3 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
252
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 321 publications
(277 citation statements)
references
References 60 publications
19
252
1
5
Order By: Relevance
“…For example, inhibitory rTMS to the non-lesioned parietal cortex can induce long-lasting improvements in symptoms of spatial neglect (Brighina et al 2003;Shindo et al 2006). In the motor region, Grefkes and colleagues showed that inhibitory rTMS applied over contralesional M1 of patients with subacute stroke significantly improved motor performance of the affected hand (Grefkes et al, 2010). This improvement was related to functional reorganization of the sensorimotor system.…”
Section: Strokementioning
confidence: 99%
“…For example, inhibitory rTMS to the non-lesioned parietal cortex can induce long-lasting improvements in symptoms of spatial neglect (Brighina et al 2003;Shindo et al 2006). In the motor region, Grefkes and colleagues showed that inhibitory rTMS applied over contralesional M1 of patients with subacute stroke significantly improved motor performance of the affected hand (Grefkes et al, 2010). This improvement was related to functional reorganization of the sensorimotor system.…”
Section: Strokementioning
confidence: 99%
“…The results of clinical studies have demonstrated that bilateral pinch gripping could enhance ipsilesional M1 excitability when compared with unilateral pinch gripping with either hand in subjects with stroke,24 which was shown by an increase in the motor evoked potential amplitude recorded from the first dorsal interosseous of the paretic hand 24. Moreover, Grefkes and colleagues23 demonstrated in a sample of 11 subjects with subacute and subcortical stroke that bilateral hand movements resulted in facilitatory neural coupling between the M1 and supplementary motor areas of the 2 cerebral hemispheres. Simultaneous activation of bilateral sensorimotor cortices via TENS might exert a similar effect of enhancing the interhemispheric interaction in both hemispheres via the corpus callosum, thus enhancing the effects of motor training.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of neuroanatomical48 and clinical23, 24 studies, the underlying mechanisms that mediate the effects of Bi‐TENS might include the enhancement of interhemispheric interaction, possibly via the corpus callosum, which is the white matter in the human brain that connects the 2 hemispheres via more than 200 million axonal connections 48. The motor areas of the 2 hemispheres have been shown with functional magnetic resonance imaging and diffusion tensor imaging to be connected via the posterior body of the corpus callosum 48.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various strategies have been shown to enhance recovery in preclinical models and patients, including pharmacological treatment, rehabilitation (e.g., constraint-induced therapy) [32][33][34], stem cell transplantation [35,36], and brain stimulation [37][38][39][40][41][42][43]. In particular, brain stimulation is a promising area of research because it allows direct activation and manipulation of the target area's excitability.…”
Section: Current Brain Stimulation Techniques Used To Study Stroke Rementioning
confidence: 99%